2016
DOI: 10.1038/srep35831
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions and self-organized criticality in networks of stochastic spiking neurons

Abstract: Phase transitions and critical behavior are crucial issues both in theoretical and experimental neuroscience. We report analytic and computational results about phase transitions and self-organized criticality (SOC) in networks with general stochastic neurons. The stochastic neuron has a firing probability given by a smooth monotonic function Φ(V) of the membrane potential V, rather than a sharp firing threshold. We find that such networks can operate in several dynamic regimes (phases) depending on the averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
0
27

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(171 citation statements)
references
References 53 publications
5
139
0
27
Order By: Relevance
“…Notice that this mean-field result is also relevant to the quenched case since, as can be seen in Fig. 5e, we have σ * → λ c = 1 for large K. This slight supercriticality has been called selforganized supercriticality (SOSC) by Brochini et al [23]. Curiously, superavalanches (the so called dragon kings) and supercriticality have also been observed in experiments [11].…”
Section: The Time Series λT and Its Fluctuationsmentioning
confidence: 68%
See 1 more Smart Citation
“…Notice that this mean-field result is also relevant to the quenched case since, as can be seen in Fig. 5e, we have σ * → λ c = 1 for large K. This slight supercriticality has been called selforganized supercriticality (SOSC) by Brochini et al [23]. Curiously, superavalanches (the so called dragon kings) and supercriticality have also been observed in experiments [11].…”
Section: The Time Series λT and Its Fluctuationsmentioning
confidence: 68%
“…Finally, the case with a = 0 only produces SelfOrganized Supercriticality (SOSC [23]). However, for large number of synapses K, as suggested by biology, networks which are almost critical are obtained, and this can be sufficient to deal with the power laws found in experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We use discrete-time stochastic integrate-and-fire neurons [14,27,28]. A Boolean variable denotes if a neuron fires (X[t] = 1) or not (X[t] = 0) at time t. The membrane potentials of neurons in E and I populations evolve as:…”
Section: The Modelmentioning
confidence: 99%
“…A growing body of evidence in the past few decades has emerged suggesting that many 2 disparate natural and particularly biological phenomena reside in a critical regime of 3 dynamics on the cusp between order and disorder [1][2][3][4][5][6][7][8][9][10]. This seemingly ubiquitous 4 phenomena has sparked a renaissance of new ideas attempting to understand the 5 self-organizing nature of our world [11].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence in the past few decades has emerged suggesting that many 2 disparate natural and particularly biological phenomena reside in a critical regime of 3 dynamics on the cusp between order and disorder [1][2][3][4][5][6][7][8][9][10]. This seemingly ubiquitous 4 phenomena has sparked a renaissance of new ideas attempting to understand the 5 self-organizing nature of our world [11]. More specifically, it has been shown that 6 critical models, and in particular the Ising model at criticality, model the statistics of 7 brain dynamics quite well [12][13][14][15], which combined with evidence of critical variables in 8 brain dynamics has led to the emergence of the critical brain hypothesis [8,10].…”
Section: Introductionmentioning
confidence: 99%